Comparing the Impact of Traditional vs. Modern Music in Aerobic Dance on Cardiovascular Endurance Improvement - Poppy Elisano Arfanda; Ians Aprilo; Arimbi; Noortje Anita Kumaat; Heryanto Nur Muhammad (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to compare the effect of aerobic dance accompanied by traditional and modern music on increasing the cardiovascular endurance of students. The research design used was a quasi-experiment with a pretest-posttest group design. The sample consisted of 40 students of Makassar State University who were divided into two groups: an aerobic dance group with traditional South Sulawesi music and an exercise group with popular modern music. The exercise was carried out for six weeks, three times a week, for 45 minutes per session. Data were collected through a multistage test (beep test) to measure VO₂ max and analyzed using parametric statistical tests. The results showed that both groups experienced a significant increase in cardiovascular endurance (p < 0.05). However, a greater increase occurred in the traditional music group (Δ = 3.34) than in the modern music group (Δ = 2.39). These findings indicate that traditional music accompaniment is more effective in increasing cardiovascular endurance and providing added value in the context of preserving local culture.